Rethinking and Intersectionally Deconstructing Contemporary Sex Workers Rights in England and Wales - Ackhurst, Molly (Kent Law Review, 2016)
Sex work and the laws that surround the selling of sexual acts have been always been plagued by debate, and these discussions are becoming increasingly more volatile. This paper attempts to breach the widening chasm between the two sides and explore the various tensions that exist. Through an exploration of intersectional methods, the theory surrounding legal deconstruction, and newer legal models in England and Wales such as the Merseyside model, this paper illustrates that dismantling the law is not enough. It is instead vital to continually investigate creative ways to use law to protect and support all sex workers, and especially those who reside in the periphery.